The Involvement Of Teachers And Peers In Providing Knowledge On Adolescent Reproductive Health At State Vocational High School 2 Bengkulu City In 2023 - Fitri Ramadhaniati; Neng Kurniati; Asmariyah Asmariyah; Linda Yulyani (Jurnal EduHealth, 2023)
Reproductive health plays an important role in escorting adolescents towards achieving healthy reproduction. Adolescent knowledge about reproductive health still needs attention. Based on demographic and family health survey data, it was found that adolescent reproductive knowledge is still relatively low with an achievement rate of 33 percent of adolescents who know about the fertile period. In addition, the percentage of smoking and consuming alcoholic beverages in adolescent boys is still relatively high, namely 55 percent and 37 percent. Bengkulu City as the capital of the Bengkulu Province is a source of various health information. Bengkulu City also has the highest number of high schools in Bengkulu Province. State Vocational High School 2 in Bengkulu City is the best vocational high school in Bengkulu city. Based on initial surveys that have been conducted, adolescents are still found to be less knowledgeable about reproductive health. This study aims to determine the involvement of teachers and peers in providing information about reproductive health. This research is an analytical descriptive research with a cross sectional approach. The sample in this study was 39 students of State Vocational High School 2 Bengkulu City who were taken by accidental random sampling. Data collection was conducted through guided interviews using electronic research questionnaires. The analysis was carried out univariately and bivariately. The results showed that there was a significant relationship between teachers involvement in schools with adolescent reproductive health knowledge with a p value of 0.03 The same was also shown in the relationship between peers involvement in providing information about reproductive health with adolescent reproductive health knowledge with a p value of 0.000. The conclusion of this study is that there is a significant relationship between teachers and peers involvement in providing information about reproductive health. Therefore, it is necessary to increase the socialization of reproductive health knowledge and counselor training for teachers in schools and peers.